Contributions of troubleshooting for the training of mathematics teachers through didactic engineering (Research, Society and Development, 2019)
It is necessary to break with some paradigms of difficulties existing in education if we crave more competent and skilled teachers in the conduct of their classes, with more ownership and focus on teaching. In this context, it is perceived that it is crucial to combine proposals that contribute to this scenario. We will highlight the focus in the research with Didactic Engineering and in teaching, the proposal of Problem Solving. In this way, the present work has as objective to discuss the insertion of the methodology of Problem Solving, through Didactic Engineering, in the training of mathematics teachers, seeking to reflect on the teaching position in the classroom, in a way that leads the student to experience the working atmosphere of a mathematician.